SISTEM PENDIDIKAN ISLAM DI INDONESIA DAN UPAYA MENBANGUN PENDIDIKAN NASIONAL YANG BERKARAKTER MULTIKULTURAL - Sapruni, Sapruni; Amin, Alfauzan; Zubaedi, Zubaedi; Ismail, Ismail; Aprianti, Nefi (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Indonesia is a country that has a variety of cultures and customs attached to a variety of ethnicities, races, cultures and religions. So that a multicultural education is needed, namely education that respects differences, so as not to become a source of conflict and division. One of the important objectives of the concept of multicultural education is to help learners to acquire knowledge, and appreciate others of different ethnicities, cultures and personality values. Multicultural education has four values, namely: Equality Value, Tolerance Value, Democratic Value, and Pluralism Value. The above values have views that complement each other in responding to multiculturalism education. National Identity is a national personality or national identity, namely characteristics or characteristics, feelings or beliefs, culture or habits owned by a nation that distinguish one nation from another. Indonesia's national identity is pluralistic consisting of a fundamental identity, namely Pancasila, an instrumental identity, namely the 1945 Constitution.